The Impact of One-, Two- and Three-component Hydraulic Road Binder on the Properties of the Hydraulically Bound Mixture. (2015) - Buczyński, Przemysław; Lech, Maciej
Abstract: The paper presents the results of tests on road base used in the construction and maintenance of roads stabilised with hydraulic binders. Seven hydraulic binder mixes were prepared under laboratory conditions by mixing three basic components: Portland cement CEM I 32.5 R, fluidized bed combustion ash (PF) and cement kiln dust (CKD). The proportions of the binder components were established in accordance with the experimental design. The percentage share of the hydraulic road binder in the bound mix was 6%. Two types of natural aggregates were used for the base. The percentage shares of the individual components in the mix were designed using the Proctor method. For pastes, made from binders, basic mechanical properties were determined. To assess the effect of binders on the properties of the base stabilised with hydraulically bound mixtures tests were conducted to measure the following: compressive strength after 7, 14, 28 and 42 days of curing, freeze-thaw resistance. Experimental results demonstrate that it is possible to determine the optimal composition of hydraulic binders for the required strength class of the base course.